Dielectric Resonator Antennas: Basic Concepts, Design Guidelines, and Recent Developments at Millimeter-Wave Frequencies - S. Keyrouz; D. Caratelli (International Journal of Antennas and Propagation)
An up-to-date literature overview on relevant approaches for controlling circuital characteristics and radiation properties of dielectric resonator antennas (DRAs) is presented. The main advantages of DRAs are discussed in detail, while reviewing the most effective techniques for antenna feeding as well as for size reduction. Furthermore, advanced design solutions for enhancing the realized gain of individual DRAs are investigated. In this way, guidance is provided to radio frequency (RF) front-end designers in the selection of different antenna topologies useful to achieve the required antenna performance in terms of frequency response, gain, and polarization. Particular attention is put in the analysis of the progress which is being made in the application of DRA technology at millimeter-wave frequencies.